Academic Health Sciences Librarian Job Descriptions Do Not Frequently Reflect Emerging Skillsets and Changing Research Needs - Opuda, Eugenia (Evidence Based Library and Information Practice, 2021)
A Review of: Reed, J. B., & Carroll, A. J. (2020). Roles for health sciences librarians at college and university libraries. Issues in Science and Technology Librarianship, (94). https://doi.org/10.29173/istl42 Abstract Objective – To examine job postings for academic health sciences libraries to determine if they reflect the changing research needs of institutions of higher education and to compare these postings to similar, existing positions. Design – Mixed methods data analysis of job advertisements collected through relevant job boards and mailing lists. The authors conducted qualitative content analysis using a modified grounded theory approach, completed two cycles of coding using NVivo 12, and calculated statistical significance using Fisher’s exact test. Setting – College and university library and Association of Academic Health Sciences Libraries job boards and mailing lists between September 1, 2018 and March 1, 2019. Subjects – 104 unique posted job descriptions. Methods – The authors conducted a thorough search of posted position descriptions (PPDs) for academic health sciences librarians across a number of job boards and mailing lists between September 1, 2018 and March 1, 2019. In addition to searching ALA JobLIST, MLA Find a Job, Association of College & Research Libraries Health Sciences Interest Group (ACRL HSIG), MEDLIB-L, and ACRL Science and Technology Section (STS), the authors also hand searched alumni and general library job electronic mailing lists using relevant keyword searching. Inclusion criteria for PPDs included research support and other research-related responsibilities for the health sciences. The authors excluded any PPDs describing administrative or non-professional positions. Following review, the IRB determined that the research design did not qualify as human subjects research. After data collection, the authors categorized the PPDs using the National Network of Libraries of Medicine (NNLM) geographic regions and by the type of institution—college and university libraries (C&UL) or Association of Academic Health Sciences Libraries (AAHSL). Using modified grounded theory, the authors identified emergent themes from the PPDs and applied descriptive coding. Then, the authors merged categories to create overall themes. Using NVivo 12 to facilitate the mixed methods content analysis, the authors ran text queries to identify major themes in the position roles and responsibilities, required and preferred education, and required and preferred qualifications sections. They also noted themes they expected to see that did not emerge in the PPDs, as well as emerging roles for health sciences libraries that are identified in the literature but did not appear as major themes in the included PPDs. Finally, the authors utilized Fisher’s exact test to calculate statistical significance. Main Results – In the quantitative analysis, the authors identified 60 AAHSL and 44 C&UL PPDs out of the 104 total job postings. Positions were available from all 8 NNLM Regions and across 32 states, though they were not all equally distributed. Most of the positions (64 of the 104) were located in the NNLM Middle Atlantic, Southeastern/Atlantic, and Greater Midwest regions. The Southeastern/Atlantic and Greater Midwest regions made up nearly half of the included PPDs. However, the New England region had the most postings per capita. In the qualitative analysis, an ALA-accredited MLIS or equivalent degree emerged as a near-universal requirement across all PPDs. The authors noted that the few PPDs that did not require this degree typically referenced it in the preferred education section or described a proxy to the MLIS. Furthermore, 57% of C&UL positions compared to 27% of AAHSL positions listed preferred education (p=0.0004) that was usually related to health and science disciplines that the position supported. There was significant overlap of required qualifications for AAHSL and C&UL postings. The authors also identified a list of hard and soft skills noted in the PPDs’ required qualifications sections, including experience with specific tools, expertise in library services, and interpersonal skills. However, reportedly emerging skills in data sciences, open science, grant experience, and research impact assessment were absent in many PPDs. The authors found statistically significant differences between two themes in the PPD roles and responsibilities including collection management (p=0.0004) and systematic reviews (p=0.03). Additionally, the authors found no statistically significant differences for required qualifications between AAHLS and C&UL PPDs. They did find statistically significant differences for two preferred qualifications including the Academic of Health Information Professionals (AHIP) credential (p=0.0042) and experience with systematic reviews (p=0.0009). The AHIP credential and experience with systematic reviews were absent in the C&UL PPDs and referenced rarely in AAHSL postings. Though diversity, equity, and inclusion (DEI) qualifications were frequently referenced in C&UL PPD requirements, the authors noted that research libraries have failed to make meaningful change in diverse candidate hiring and retention, but also pointed to the rapid adoption of DEI qualifications in PPDs within a short period of time. The authors highlighted that the roles and responsibilities reflected traditional librarian duties and referenced more emerging skills and research needs than any other section of the PPD. Assessment and systematic reviews appeared more often in the roles and responsibilities sections of AAHSL and C&UL PPDs in comparison to the combined required and preferred qualifications sections of all the PPDs. A more traditional responsibility, collection management, also appeared more frequently in the roles and responsibilities section of PPDs than in the experience section, suggesting that most hiring committees feel confident that librarians who fill positions will be successful in performing collection management tasks despite experience. The authors noted that collection management, one of the most common themes that emerged from the data analysis, appeared more frequently in C&UL PPDs and theorize that AAHLS may have dedicated collection management departments. Conclusions – While the research literature documents new roles and emerging skills for academic health sciences librarian positions, the authors noted that PPDs do not frequently reflect those emerging roles and skills, and maintain traditional health sciences librarian skillsets. The authors concluded that library administrators should design position descriptions that are user centred and match the changing research needs of the local community. PPDs should reflect changing priorities by including less weight towards the MLIS degree, shifting traditional skillsets from required experience sections to preferred experience sections, adapting the language of PPDs to be more inclusive and welcoming for a diverse pool of candidates, and adding an emphasis on DEI responsibilities. By creating position descriptions that are user focused, library administrators and hiring committees make meaningful investments for their communities and their strategic priorities.